Aplikasi Sistem Pendukung Keputusan Penerimaan Staff Video Editing Menggunakan Metode Profile Matching Berbasis Web - Octaviansyah Pasaribu, A. Ferico; Saputra, Very Hendra (Jurnal Media Borneo, 2023)
Video editing staff will not only become experts in using the latest editing software, but will also play a role in crafting the narrative inherent in each production. Profile matching refers to the process of comparing the characteristics or attributes of one entity to another to find conformity or similarity. This study aims to apply the profile matching method in the acceptance of video editing staff on CV XYZ so that the ranking results of the profile matching method can be a company recommendation in determining the acceptance of video editing staff. Based on the selection of prospective video editing staff using the profile matching method, it is recommended for candidate A as a recommendation for prospective video editing staff because it gets a total score of 4.58.